Telemonitoring Temperature and Humidity at Bio-energy Process using Smart Phones - Seno Darmawan Panjaitan; Novianda Fratama; Aryanto Hartoyo; Rudi Kurnianto (Universitas Ahmad Dahlan, 2016)
Bio-energy from biogas can be produced through anaerobic digestion of either organic solid waste or wastewater. Energy production process in the digester is however sometimes hard to be monitored due to manual measurement, otherwise it needs a high technology requiring a high cost budget. This paper presents a low cost technology to monitor the process by using Android based smart phones which can easily be integrated in human daily activity. A program was built by using Eclipse in order to give send/receive command to/from the hardware and display the measurement data on the registered smart phones. The measurement controller was put at the anaerobic digester to record temperature and Relative Humidity (RH) data to memory card and to transmit the data to smart phones. In the experiment with 20 data samples, mean errors were repectively -0.317 oC, 0.932 oC, and 1,378 % for temperature sensor LM35, and temperature and RH sensor using SHT11. Mean squared error for LM35 was 0.373 oC and for SHT11 was 1.117 oC and 2.629 % for temperature and RH respectively. The system has been also implemented in the real anaerobic digester. Electrical energy consumption was 0.623 Wh with 30 minutes cycle time and one minute sampling time.